Book Review: Taoisigh and the Arts (Kevin Rafter: Martello, 2022) - Vaughan, Connell (Irish Journal of Arts Management and Cultural Policy, 2023)
Kevin Rafter’s short book is an entertaining taste of the use and abuse of the arts in Ireland by successive Taoisigh (the plural form of the title of the Irish elected head of state, ‘Taoiseach’). It covers a century of cultural policy juxtaposed with artistic responses of the times, to reveal a story of official neglect and the privileging of economic concerns. Until the establishment of the Department of Arts in 1993 only one Taoiseach truly embraced his responsibilities to the arts and Charles J. Haughey would do so in a way that emphasised grand gestures to support his image all the while continuing the underfunding of the sector. Though the powers of the role have largely transferred to the Departmental Minister, the role of Taoiseach retains a certain symbolic and diplomatic significance when it comes to the arts.